Clinical Manifestations of Herpes Zoster Associated with Complications in Children - Dong Ha Kang; Byung Ok Kwak; A Young Park; Han Wool Kim (MDPI AG, 2021)
Herpes zoster (HZ) is caused by latent varicella-zoster virus (VZV) reactivation when VZV-specific cell-mediated immunity declines. Information on HZ in children is limited. Therefore, we retrospectively investigated HZ's clinical course and complications in children. We extracted the outpatient and hospitalization medical records of pediatric patients (<19 years) primarily diagnosed with HZ (ICD-10 B02 code) between January 2010 and November 2020. HZ was defined as a typical unilateral dermatomal vesicular rash where HZ was the treating physician's primary diagnosis. Recognized HZ complications included combined bacterial skin infection, ophthalmic zoster, zoster oticus without facial paralysis, meningitis, and PHN. We identified 602 HZ cases, among which 54 developed HZ complications and were included in our analysis. The median age was 14.7 years, most patients were aged ≥13 years (42, 79%), and none were aged <4 years. Fifty-three were immunocompetent, and only one had systemic lupus erythematosus. The most frequent complication was zoster ophthalmicus (n = 26, 48%). HZ complications were also observed in immunocompetent or vaccinated children exhibiting a head or neck rash before and after VZV immunization. Current VZV vaccination programs may be insufficient in preventing HZ complications. Therefore, close varicella and HZ burden monitoring and the establishment of effective VZV vaccination programs are imperative.